PERAN GURU DALAM MENGEMBANGKAN PERILAKU ASERTIF PADA ANAK USIA DINI - Rahmat Hidayat (AZZAHRA, 2019)
Based on the phenomenon in the field of Bandar Sribhawono Pertiwi Kindergarten students, there are students who are not assertive, this study is intended to describe students' assertive behavior. In addition, this study also tries to look at the role of the accompanying teacher in improving student assertive behavior. This research uses quantitative by using descriptive methods. This study explains that assertive behavior in aspects; (1) The ability to express positive feelings is in the low category, (2) The ability to assert themselves in the medium category, (3) The ability to express negative feelings is in the low category, (4) The role of the companion teacher in improving students' assertive behavior has been applied but better efforts are still needed in service delivery.